2014
DOI: 10.5194/acp-14-12983-2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different emission inventories on modeled ozone and carbon monoxide in Southeast Asia

Abstract: Abstract. In order to improve our understanding of air quality in Southeast Asia, the anthropogenic emissions inventory must be well represented. In this work, we apply different anthropogenic emission inventories in the Weather Research and Forecasting Model with Chemistry (WRF-Chem) version 3.3 using Model for Ozone and Related Chemical Tracers (MOZART) gas-phase chemistry and Global Ozone Chemistry Aerosol Radiation and Transport (GO-CART) aerosols to examine the differences in predicted carbon monoxide (CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 63 publications
(70 reference statements)
4
33
0
Order By: Relevance
“…We do not attempt to provide a detailed quantitative estimate of the uncertainty in the magnitude of O 3 productions. In reality, the model based estimates of biomass burning impacts are subject to several sources of uncertainty including uncertainties in the magnitude of emission estimates (both FINNv1 and the anthropogenic emission inventories (Amnuaylojaroen et al, 2014), chemistry and transport, meteorology (Kumar et al, 2012a), model resolution etc. The accuracy of FINN depends on the land cover maps used and the emission factors.…”
Section: Resultsmentioning
confidence: 99%
“…We do not attempt to provide a detailed quantitative estimate of the uncertainty in the magnitude of O 3 productions. In reality, the model based estimates of biomass burning impacts are subject to several sources of uncertainty including uncertainties in the magnitude of emission estimates (both FINNv1 and the anthropogenic emission inventories (Amnuaylojaroen et al, 2014), chemistry and transport, meteorology (Kumar et al, 2012a), model resolution etc. The accuracy of FINN depends on the land cover maps used and the emission factors.…”
Section: Resultsmentioning
confidence: 99%
“…GFAS, as a priori emission, is used to optimize CO emissions using observations from the Infrared Atmospheric Sounding Interferometer (Krol et al, 2013). FINN is employed to predict surface ozone and CO production (Amnuaylojaroen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al () also pointed out that substantial uncertainties exist in the estimated emissions, especially for regions experiencing rapid changes in the economy such as China and India. For instance, a comparison of different anthropogenic emission inventories using WRF‐Chem over Southeast and South Asia has been performed in Amnuaylojaroen et al () and Sharma et al (). Amnuaylojaroen et al () showed that the uncertainties of carbon monoxide surface mixing ratios in simulations with different anthropogenic emission inventories reach 30%.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a comparison of different anthropogenic emission inventories using WRF-Chem over Southeast and South Asia has been performed in Amnuaylojaroen et al (2014) and Sharma et al (2017). Amnuaylojaroen et al (2014) showed that the uncertainties of carbon monoxide surface mixing ratios in simulations with different anthropogenic emission inventories reach 30%. Sharma et al (2017) showed that the modeled ozone mixing ratios during noontime are sensitive to the choice of an emission inventory.…”
Section: Introductionmentioning
confidence: 99%